ДОСЛІДЖЕННЯ ПОКАЗНИКІВ ПРОДУКТИВНОСТІ ЕЛЕКТРОМАГНІТНОГО МЛИНА - Макарчук, О.; Цалус, Д. (Інститут електродинаміки НАН України, Київ, 2022)
The paper is devoted to the development of a way for quantitative evaluation of the performance of an electromagnetic mill, i.e. a device that converts electrical energy into energy of mechanical interaction of operating elements (millstones) with the substance being ground/mixed. The proposed way is based on processing the results of calculating the trajectories of ferromagnetic millstones of an electromagnetic mill moving in a rotating magnetic field under the action of electrodynamic forces and hydrodynamic resistance forces and limited by the space of the working chamber. The average values of the number of blows, the momentum of the force of these blows, the linear velocity of the millstones and the value of the jerk are calculated. The proposed expression for calculating the integrated non-dimensional performance indicator is calculated on the basis of the above values and allows to link the performance of the grinding process with the design indicators of the mill inductor, the size of its working chamber, quantity, shape, dimensions of millstones, etc. The results of mathematical experiments to determine this performance indicator for an electromagnetic mill with a working volume of 2090 cm3 and an average value of magnetic induction in the working chamber ≈ 0.12 T are specified. This way needs an experimental confirmation. References 11, figures 5, table 1.